Strategiczne porozumienia ponad podziałami – Grupa Wyszehradzka jako przykład integracji i emancypacji w ramach Unii Europejskiej - Grodzki, Radosław (Przegląd Strategiczny, 2016)
Functioning of the Visegrad Group since its beginning was not an easy issue. V4 was established to integrate East-Central European countries into Euro-Atlantic structures in the atmosphere of cooperation. However, it was a partnership o f countries which in many cases guided by different interests. From the beginning, there was no sympathy inside the Group, but over time it changed. Since joining into the European Union in this cooperation experienced moments of common mobilizing such as: a struggle under the EU Cohesion Policy, the fight for the Union budgets, and the last one position against the welcome of refugees arriving to Europe. It should be noted that properly develop cooperation of Visegrad Group at the elementary level in areas such as: environmental protection, infrastructure, transport and energy projects and tourism. An important new motivation to this cooperation is founded in 2016 EU Battle Group of the Visegrad Group with almost 4 thousand soldiers.